2018
DOI: 10.1108/ebhrm-12-2017-0063
|View full text |Cite
|
Sign up to set email alerts
|

Total rewards components and work happiness in new ventures

Abstract: Purpose The purpose of this paper is to examine the influence of total rewards components (monetary, material and non-monetary) on happiness of employees working in Indian technology-based new ventures. Further, with the theoretical lens of social exchange theory, the mediating role of work engagement between total rewards perceptions and work happiness relationship has also been evaluated. Design/methodology/approach A survey of 201 employees working in Indian technology-based new ventures was conducted. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 65 publications
4
21
0
2
Order By: Relevance
“…This study found that WLBP, DCOP, WCP, and WLP correlated significantly and positively with work engagement. The obtained results corroborate the finding of a previous study (Gulyani and Sharma, 2018 ), which indicated that a high level of monetary rewards and non-monetary rewards may foster employee engagement in work. Employees who were offered a reward package that is consistent with their personal preferences were more likely to engage in work (Pregnolato et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study found that WLBP, DCOP, WCP, and WLP correlated significantly and positively with work engagement. The obtained results corroborate the finding of a previous study (Gulyani and Sharma, 2018 ), which indicated that a high level of monetary rewards and non-monetary rewards may foster employee engagement in work. Employees who were offered a reward package that is consistent with their personal preferences were more likely to engage in work (Pregnolato et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, Social Identity Theory states that the strong relationship between employees and the organization may motivate employees to give their best for the organization (Brown, 2017 ; Pan et al, 2019 ) and increase their level of engagement (Wang and Tseng, 2019 ). When kindergarten teachers get the expected economic or non-economic rewards from the organization, in return, they will have a stronger sense of identity with kindergarten, form a positive psychological state, and immerse themselves in their work (Blau, 1986 ; Gulyani and Sharma, 2018 ). The Conservation of Resources Theory proposes that individuals with more resources not only will try their best to maintain and protect their existing resources but also are more capable of acquiring new resources (Hobfoll, 1989 , 2011 ), thus exhibiting more positive mental states and behaviors (Halbesleben and Wheeler, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employee engagements benefits in creating a sense of recognition, trained workforce etc. Employee engagement programmes have to be implemented with caution, as the eco-system of startups differs significantly from large corporate (Weiblen and Chesbrough, 2015;Manning, 2016;Gulyani and Sharma, 2018).…”
Section: Antecedents Of Strategic Management and Its Interrelationship With Employee Engagement And Skill Developmentmentioning
confidence: 99%
“…(Chinyio et al, 2018), a study of a sample of 260 respondents of Jigawa state public sectors, stated that compensation elements "salary; pension; gratuity; and bonuses" have a positive influence with "attraction; motivation; job satisfaction; Open Journal of Business and Management and retention of the public sector". In addition, (Gulyani & Sharma, 2018), the study proposed that total reward systems have a strong influence on the personnel's work engagement and happiness at work. Specifically, the pay is considered one of the key factors and individually equivalents four times compared to other compensation factors (Addis et al, 2018).…”
Section: Overall Compensation Benefits and Job Satisfactionmentioning
confidence: 99%